Prioritising the cultural inclusivity of a rural mainstream health service for First Nation Australians: an analysis of discourse and power. Issue 3 (2nd September 2018) - Malatzky, Christina; Nixon, Raelene; Mitchell, Olivia; Bourke, Lisa
ABSTRACT: In the context of persisting health inequities within many multicultural and socially diverse countries like Australia, there is a call for health services to implement culturally inclusive systems and practices. Nowhere is this more important than in regional, rural and remote Australia where consumers are diverse, health services are scarce, and services designed for particular groups of the population are lacking. Drawing on interviews with 20 staff of a rurally-based, mainstream community health service, this article examines the role of discourse in the transition to a culturally inclusive health centre. In doing so, the power struggles inherent in such a process are highlighted. The article contends that improvements in the health outcomes of First Nation and culturally Other groups within the Australian population is contingent upon systematic resistances that disrupt and re-arrange existing dominant discourses. This calls for a disruption of current race relations in both broader social fields as well as those supporting biomedical assumptions about the delivery of healthcare in the mainstream health sector. Alternative discourses must be promoted in both these fields.